2015
DOI: 10.1053/j.ajkd.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Study of Living Kidney Donors: Three-Year Follow-up

Abstract: Background There have been few prospective controlled studies of kidney donors. Understanding the pathophysiological effects of kidney donation is important for judging donor safety and for improving our understanding of the consequences of reduced kidney function in chronic kidney disease. Study Design Prospective, controlled, observational cohort study. Setting & Participants Three-year follow-up of kidney donors and paired controls suitable for donation at their donor’s center. Predictor Kidney donati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
116
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 51 publications
14
116
1
4
Order By: Relevance
“…We found 9 studies, 614 not including the current study 15, 16 reporting possible mineral and bone disorders in kidney donors (Table S1). Of the previous 9 studies, 5 were prospective, comparing changes before and after donation but did not include normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found 9 studies, 614 not including the current study 15, 16 reporting possible mineral and bone disorders in kidney donors (Table S1). Of the previous 9 studies, 5 were prospective, comparing changes before and after donation but did not include normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…16 Despite reduced levels of serum phosphate, tubular resorption of phosphate declined (Table 3), indicating that renal phosphate excretion was the likely cause, or at least a contributing factor to the lower serum phosphate concentrations. Although 3 studies reported no change in serum phosphate concentrations, 6, 10, 14 3 others reported a decline in phosphate after kidney donation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations